Everybody's book of bicycle riding - Lieb, Thom. (Pennsylvania : Rodale Press, 1981)
This book is my attempt to correct the situation. i've tried to cover everything of interest to the novice cyclist, with special emphasis on making cycling easier, safer, more comfortable and ultimately, more enjoyable.
Part 1. Warming up -- Part 2. Getting into gear -- Part 3. Getting started -- Part 4. Getting better -- Part 5. Staying on the road.
Includes index.
Keywords: CYCLING